Proteomic analysis of Taenia hydatigena metacestode by high performance liquid chromatography-coupled tandem mass spectrometry (LC-MS/MS) - TAOXIANG, HAI; BAO-CHENGHAO, BAO-CHENGHAO; XING, XIAO-YONG; FENG-QINWEN, FENG-QINWEN (The Indian Journal of Animal Sciences, 2018)
This study determined the profile of proteins in T. hydatigena metacestode by LC-MS/MS. Furthermore, comparison of 6 tapeworms revealed the presence of Taenia-specific filamin proteins and Echinococcus-specific UGPase proteins. These data provide clues for better understanding of T. hydatigena biological characteristics, which provides a new choice for screening of new diagnostic antigens for differential diagnosis of diseases by coinfections of various tapeworm metacestodes.